Nonlinear cavity optomechanics with nanomechanical thermal fluctuations - Rick Leijssen (Nature Portfolio, 2017)
Optomechanical experiments often assume linear coupling between optical fluctuations and mechanical displacements. Here, Leijssenet al. experimentally demonstrate the nonlinear interaction from thermally induced fluctuations in a sliced nanobeam cavity with high cooperativity.